Photovoltaics performance improvement using different cooling methodologies: A state-of-art review. (10th November 2020) - Kandeal, A.W.; Thakur, Amrit Kumar; Elkadeem, M.R.; Elmorshedy, Mahmoud F.; Ullah, Zia; Sathyamurthy, Ravishankar; Sharshir, Swellam W.
Abstract: Photovoltaic (PV) panels, being an eco-friendly technology, have become a crucial source of electricity, satisfying the increasing energy demand and substituting the related shortage occurring in the conventional energy sources. Despite absorbing about 80% of incident radiation, PV cells have low conversion efficiency; hence, a minor portion of the absorbed radiation is gained as electrical power, and the majority is converted into heat increasing the panel temperature. Undesirably, the higher panel temperature, the lower conversion performance, and lesser reliability over the long term occur. Hence, many cooling systems have been designed and investigated, aiming to effectively avoid the excessive temperature rise. This paper aims to review and merge the recent cooling methods investigations on PV, categorizing them according to heat transfer modes: convective cooling (hydro and aero-based cooling with or without extended surfaces), conductive cooling (phase change materials), and radiative cooling. Each category and corresponding works are discussed in detail, and main resulted enhancements, with respect to uncooled PV panels, are presented. In addition, applications of hybrid photovoltaic-thermal systems are clarified with indicating main improvements in their electrical, thermal, and overall efficiencies. It expected that the presented work can provide a new comprehensive taxonomy for cooling techniques applied to photovoltaics. Highlights: A deep survey on the state-of-the-art aspects of PV cooling is presented. A new comprehensive taxonomy for cooling methodologies including nanofluid-based PVT are proposed. Enhancements of thermo-electric performance of PVT systems are discussed. Improved convective cooling via extended surfaces is surveyed. Radiative cooling performance of PV modules, and corresponding applications are reviewed.